Physico-chemical and Phyto-chemical Standardization of a Potent Unani Cardiovascular drug Saad Kufi (Cyperus scariosus R. Br) - Nafees, Sana; Nafees, Huda; Rehman, Sumbul; Rahman, Syed Ziaur; Yousuf Amin, Kunwar Mohammad (Bangladesh Journal of Medical Science, 2022)
Background: Standardization of a single potent Unani drug Saad Kufi is a must for maintaining and assessing the quality and safety as to attain the desired therapeutic effect. This will help prepare the ideal monograph which will serve in establishing its authenticity, quality, safety and reproducibility. Aim: The study aims to prepare the ideal monograph of the Saad Kufi (Cyperus scariosus R.Br)which is an important cardiovascular drug. Methodology: Physicochemical and preliminary phytochemical analyses were carried out according to the guidelines given by WHO. Result: Saad Kufi powder was coarse, brown incolor, Agreeable smell, and Tasteless. Total ash, acid insoluble ash, water-soluble ash, loss in weight on drying, pH (1% and 10% solution) were found to be16.3±0.07, 8.616±0.20, 3.1±0.30, 8.5±0.173, 5.76±0.08 and 5.23±0.08 respectively. The crude fibre content was 46.43±0.19 The Phytochemical screening revealed the presence ofalkaloids, carbohydrates, proteins, phenols, sterols, glycosides, Cardiac glycosides, flavonoids, sterols/ terpenes and volatile oil. TLC studies of various extracts of drugs obtained in different solvent system have been conducted and Rf values of various spots in different solvent systems have been noted in day light, UV light and after treatment with iodine vapours. The Rf values in the given solvent are used to characterize the drugs identity and purity. Conclusion: The above findings could be considered for laying down pharmacopoeial standards. No data exhibits in this regard to compare with, thus our findings may be considered as standard for future references. Bangladesh Journal of Medical Science Vol. 21 No. 04 October’22 Page : 858-864